Influence of social networking on the psychological adjustment of adolescents with hearing impairment in Ibadan, Oyo State, Nigeria (2015)
This study investigated the influence of social networking (SN) on the psychological adjustment of adolescents with hearing impairment in Oyo State, Nigeria. The study adopted a descriptive survey research design. A purposive sampling technique was employed to select adolescents with hearing impairment. A simple random sampling technique was also used to select 126 adolescents with hearing impairment who were thirteen years and twenty three years of age from both the junior and the senior secondary schools in Ibadan, Oyo State. 3 research questions were generated and one hypothesis was formulated. Data were collected through a structured questionnaire tagged “Social Networking (Social Media) Scale” with a reliability coefficient of 0.74. Data were analysed with inferential statistics of Pearson Product Moment Correlation, Multiple regression and Analysis of Variance (ANOVA). The findings revealed that use of SN have a positive significant relationship with emotional intelligence (r = .601; P < .05) and self-esteem (r =.280; P < .05) while SN has an insignificant relationship with loneliness (r = -0.150, p > 0.05) among adolescents with hearing impairment. The finding also found a joint relationship between use of SN, emotional intelligence, self esteem and loneliness (F(3,125) = 33.052, P < 0.05). The study found no significant difference in the use of SN among male and female adolescents with hearing impairment (t = 0.796; df =124; p > 0.05). The study concluded that use of SN have a great influence on psychological well-being, access to information, sustaining relationships and self expression among adolescents with hearing impairment. Based on these findings, it was recommended that adolescents with hearing impairment should be actively involved in physical and social activities with their hearing peers in order to boost their self esteem and emotional intelligence while it will eliminate issues of social isolation and facilitate social inclusion.